Adiponectin attenuates human eosinophil adhesion and chemotaxis: implications in allergic inflammation. (17th July 2013) - Yamamoto, Rie; Ueki, Shigeharu; Moritoki, Yuki; Kobayashi, Yoshiki; Oyamada, Hajime; Konno, Yasunori; Tamaki, Mami; Itoga, Masamichi; Takeda, Masahide; Ito, Wataru; Chihara, Junichi
Abstract: Objective: Growing evidence has shown an association between obesity and asthma. Adiponectin, an adipocyte-derived cytokine, is known to have anti-inflammatory effects with reduced concentrations in obese subjects. Recent findings raised the intriguing possibility that adiponectin might play a role in allergic inflammation, although the mechanistic basis for their relationship remains unclear. The purpose of this study was to examine whether adiponectin might affect functions of eosinophils, which play an important role in the pathogenesis of asthma. Methods: Human peripheral blood eosinophils were purified to study expression of adiponectin receptors AdipoR1 and AdipoR2 using RT-PCR and flow cytometry. The effect of adiponectin on eosinophil survival was investigated using annexin V and propidium iodide staining. Eotaxin-induced cell adhesion was investigated using ICAM-1-coated plates. A Boyden chamber and real-time horizontal migration system were used for eotaxin-directed chemotaxis assay. Expression of eotaxin receptor CCR3 and intracellular calcium influx were assessed by flow cytometry. Results: AdipoR1 and AdipoR2 were expressed in human eosinophils. Adiponectin did not affect eosinophil survival or CCR3 expression; however, eotaxin-enhanced adhesion was inhibited by pretreatment with adiponectin. Adiponectin also diminished eotaxin-directed chemotactic responses by disturbing both velocity and directionality. Calcium influx in response to eotaxin was attenuated by adiponectin. Conclusions: These results indicate that adiponectin attenuates the eosinophil functions induced by eotaxin without affecting cell viability. The inhibitory effect was associated with diminished calcium signaling rather than altering of surface receptor expression. Increasing circulating adiponectin might be a novel therapeutic modality for treatment of asthma, especially in obese asthmatics.